PENGARUH DISKON, FLASH SALE, DAN PENGGUNAAN SISTEM PEMBAYARAN DIGITAL TERHADAP KEPUTUSAN PEMBELIAN DI TOKO I AM FASHION STORE BENGKULU - Ardi Aprinawan Popi; Mimi Kurnia Nengsih (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
The main objective of this study is to analyze how much the variables of promotion and digital payment systems influence consumer purchase decisions. This type of research is a quantitative research, this research is a buyer of products sold at I am Fashon store Bengkulu. The sample extraction method uses proportional sampling or balanced sampling techniques. The number of respondents in this study was 120 people. The data collection method used questionnaires. Data analysis techniques using multiple linear regression analysis tests, determination coefficient analysis, and hypothesis tests. Based on the results of data processing, from the computer calculation, namely using SPSS 25, the regression equation is Y = 1.230 + 0.178X1 + 0.381 X2 + 0.356X3 + ei with a value of R Square R2 = 0.562 this value means that independent contributes 56.2% in influencing the dependent variable. The results of the hypothesis test obtained Discounts, Flash Sale, and Digital Payment Systems together have a positive and significant effect on the Purchase decision. Keywords: Discounts, Flash Sale, Digital Payment Systems, Purchase Decisions.